2010
DOI: 10.1016/j.biomaterials.2010.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Doubly amphiphilic poly(2-oxazoline)s as high-capacity delivery systems for hydrophobic drugs

Abstract: Solubilization of highly hydrophobic drugs with carriers that are non-toxic, non-immunogenic and well-defined remains a major obstacle in pharmaceutical sciences. Well defined amphiphilic di- and triblock copolymers based on poly(2-oxazolines) were prepared and used for the solubilization of Paclitaxel (PTX) and other water-insoluble drugs. Probing the polymer micelles in water with the fluorescence probe pyrene, an unusual high polar microenvironment of the probe was observed. This coincides with an extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
356
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(370 citation statements)
references
References 47 publications
10
356
1
3
Order By: Relevance
“…Two glass-transistions were detected, indicative of the immiscibility of the two types of blocks in the amphiphilic copoly(2-oxazoline). Kabanov et al synthesized amphiphilic di-and triblock copolymers of the compositions pEtOx-block-p n BuOx and pMeOx-block-p n BuOx-block-pMeOx [179]. These block copolymers formed micelles in water and were used to solubilize otherwise water-insoluble drugs like Paclitaxel.…”
Section: Self-assembly Of Triblock Copoly(2-oxazoline)smentioning
confidence: 99%
“…Two glass-transistions were detected, indicative of the immiscibility of the two types of blocks in the amphiphilic copoly(2-oxazoline). Kabanov et al synthesized amphiphilic di-and triblock copolymers of the compositions pEtOx-block-p n BuOx and pMeOx-block-p n BuOx-block-pMeOx [179]. These block copolymers formed micelles in water and were used to solubilize otherwise water-insoluble drugs like Paclitaxel.…”
Section: Self-assembly Of Triblock Copoly(2-oxazoline)smentioning
confidence: 99%
“…However, the use of poly(2-alkyl-2-oxazolines) in drug delivery so far is not well covered, and the research is focused mainly on the systems which increase the solubility of hydrophobic drugs. Luxenhofer et al reported for the synthesis of di-and tri-block copolymers based on poly(2-oxazolines) for the solubilization of water-insoluble drugs (24). Han Y. et al used amphiphilic poly(2-oxazoline)s micelles as a promising high-capacity delivery platform carrying synergistic combinations of multiple chemotherapeutic agents for multidrug cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to assess the feasibility of formulating lipospheres of Pioglitazone HCl by melt dispersion technique and obtaining a suitable release pattern. [1][2][3][4][5] cetyl alcohol, gelatin were purchased from S.D. Fine Chemicals Ltd. (India).…”
Section: Introductionmentioning
confidence: 99%